Education in Prison is not Only an Activity - Marc De Maeyer (Educação & Realidade, 2013)
Education and prison have always formed an incoherent pair: the first, finding its universal reasons in the particular context of the second, which, by its nature, offers only a contradictory frame for the free expression of the first one. How can prison, being anti-educative by itself, offer people an opportunity to explore useful knowledge from now until the day they are released? We will try to demonstrate that, amidst these contradictions, education is possible with the proviso that it is effectively an education for life, and not only instruction or reeducation.